Structure of LIMP-2 provides functional insights with implications for SR-BI and CD36 - Neculai, Dante; Schwake, Michael; Ravichandran, Mani; Zunke, Friederike; Collins, Richard F.; Peters, Judith; Neculai, Mirela; Plumb, Jonathan; Loppnau, Peter; Pizarro, Juan Carlos; Seitova, Alma; Trimble, William S.; et al. (Nature, 2013)
Members of the CD36 superfamily of scavenger receptor proteins are important regulators of lipid metabolism and innate immunity. They recognize normal and modified lipoproteins, as well as pathogen-associated molecular patterns. The family consists of three members: SR-BI (which delivers cholesterol to the liver and steroidogenic organs and is a co-receptor for hepatitis C virus), LIMP-2/LGP85 (which mediates lysosomal delivery of β-glucocerebrosidase and serves as a receptor for enterovirus 71 and coxsackieviruses) and CD36 (a fatty-acid transporter and receptor for phagocytosis of effete cells and Plasmodium-infected erythrocytes). Notably, CD36 is also a receptor for modified lipoproteins and β-amyloid, and has been implicated in the pathogenesis of atherosclerosis and of Alzheimer's disease. Despite their prominent roles in health and disease, understanding the function and abnormalities of the CD36 family members has been hampered by the paucity of information about their structure. Here we determine the crystal structure of LIMP-2 and infer, by homology modelling, the structure of SR-BI and CD36. LIMP-2 shows a helical bundle where β-glucocerebrosidase binds, and where ligands are most likely to bind to SR-BI and CD36. Remarkably, the crystal structure also shows the existence of a large cavity that traverses the entire length of the molecule. Mutagenesis of SR-BI indicates that the cavity serves as a tunnel through which cholesterol(esters) are delivered from the bound lipoprotein to the outer leaflet of the plasma membrane. We provide evidence supporting a model whereby lipidic constituents of the ligands attached to the receptor surface are handed off to the membrane through the tunnel, accounting for the selective lipid transfer characteristic of SR-BI and CD36. © 2013 Macmillan Publishers Limited. All rights reserved.
CRIS-Team Scopus Importer:2020-10-21